Corporate social responsibility and zero leverage - Uz Zaman, Qamar; Ehsan, Sadaf; Hassan, Mohammad Kabir; Javed, Muzhar; Ul Hassan, Syed Iftikhar (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper aims to investigate the link between Corporate Social Responsibility (CSR) and Zero Leverage (ZL) policy of firms. We use panel logistic multivariate regression to determine the socially responsible behavior of ZL firms and their levered counterparts. Our proxies for CSR are corporate social responsibility disclosure and corporate tax contribution against the proxies of ZL and almost zero-leverage (AZL). The sample firm-year observations of Pakistani listed firms from 2009-2018 are further divided in subsamples for short term ZL and long term ZL firms. We also test the constraints hypothesis for our sample firms. We found that CSR and ZL policy complement each other, adding to the firm’s financial and social sustainability. The positive relationship between CSR and ZL is more significant in dividend-paying firms. Further, results support that financially unconstrained socially responsible firms have more probability to choose ZL or AZL policy. This study provides initial evidence regarding the relationship between CSR behavior and ZL policy of firms. Further, this study is the pioneer to introduce tax contribution as a proxy of CSR.